Ethanol-wet bonding technique: Clinical versus laboratory findings. Issue 9 (September 2015) - Kuhn, Eunice; Farhat, Patrícia; Teitelbaum, Ana Paula; Mena-Serrano, Alexandra; Loguercio, Alessandro D.; Reis, Alessandra; Pashley, David H.
Highlights Ethanol and water-wet bonding were evaluate under clinical and laboratory conditions. It is one of the first studies that evaluated the ethanol wet-bonding in an in vivo condition. Results in the laboratory setting was not confirmed in clinical conditions. Based on nanoleakage results, ethanol wet-bonding is a promise technique.